Thermalization and free decay in surface quasigeostrophic flows - Teitelbaum, Tomas (2012)
We derive statistical equilibrium solutions of the truncated inviscid surface quasigeostrophic (SQG) equations, and verify the validity of these solutions at late times in numerical simulations. The results indicate the pseudoenstrophy thermalizes while the pseudoenergy can condense at the gravest modes, in agreement with previous indications of a direct cascade of pseudoenstrophy and an inverse cascade of pseudoenergy in forced-dissipative SQG systems. At early times, the truncated inviscid SQG simulations show a behavior reminiscent of forced-dissipative SQG turbulence, and we identify spectral scaling laws for the pseudoenergy and pseudoenstrophy spectra. More importantly, a comparison between viscous and inviscid simulations allows us to identify free-decay laws for the pseudoenstrophy in SQG turbulence at very large Reynolds number. © 2012 American Physical Society.